CESifo World Economic Survey August 2005 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2005)
World Economic Climate: World Economic Climate stabilizes - Economic Expectations: Assessments of current economic situation slightly downgraded, economic expectations somewhat more positive - Inflation: Stable rate expected in 2005 - Interest Rates: Trend of rising rates will level off - Currencies: Euro seen to a lesser degree as overvalued - Special Topic: The role of the Internet
Keywords: 330